THE PHENOMENON OF CODE-SWITCHING AS PRACTICED AMONG CHEFS - Satria Rusdy Wijaya; Saroh Fitriani (Media Bina Ilmiah, 2024)
This paper aims to investigate whether language use can account for the differences in code-switching within the article-noun phrase in children exposed to English and German, French and Russian, and English and Polish. It investigates two aspects of language use: equivalence and segmentation. Four children’s speech is derived from corpora of naturalistic interactions recorded between the ages of two and three and used as a source of the children’s article-noun phrases. We demonstrate that children’s CS cannot be fully explained by structural equivalence in each two languages: there is CS in French-Russian although French does, and Russian does not, use articles. We also demonstrate that language pairs which use higher numbers of articles types, and therefore have more segmented article-noun phrases, are also more open to switching. Lastly, we show that longitudinal use of monolingual articles-noun phrases corresponds with the trends in the use of bilingual article-noun phrases. The German-English child only starts to mix English articles once they become more established in monolingual combinations while the French-Russian child ceases to mix French proto-articles with Russian nouns once target articles enter frequent use. These findings are discussed in the context of other studies which report code-switching across different language pairs